Effects of heart rate vs. speed-based high intensity interval training on aerobic and anaerobic capacity of female soccer players - Arazi, H.; Keihaniyan, A.; EatemadyBoroujeni, A.; Oftade, A.; Takhsha, S.; Asadi, A.; Ramirez-Campillo, R. (Sports, 2017)
The purpose of this study was to compare the effects of two types of high-intensity interval training (HIIT) programs on aerobic and anaerobic capacity of female soccer players. Regional-level female athletes were randomly divided into heart rate-based HIIT (n = 8; age 23.4 ± 1.1 year) and speed-based HIIT groups (n = 8; age 23.4 ± 1.3 year). Athletes trained three days per week for six weeks. Before and after training, each athlete`s performance was assessed directly through the Hoff test, 30-15 Intermittent Fitness Test (VIFT), and repeated-sprint ability test (RAST); maximal oxygen consumption (VO2max), power and fatigue were estimated indirectly. Both experimental groups improved power, fatigue index and VO2max after training (p < 0.05). It was noteworthy that the speed-based group had greater gains in minimal power (effect size (ES): 3.99 vs. 0.75), average power (ES: 2.23 vs. 0.33), and fatigue index (ES: 2.53 vs. 0.17) compared to heart rate-based group (p < 0.05). In conclusion, both heart rate-based and speed-based HIIT induced meaningful improvements in power, VO2max, and fatigue index in female soccer players, although the speed-based HIIT group achieved greater gains in power and fatigue index compared to the heart rate-based group